Cradle of life : the discovery of earth's earliest fossils - Schopf, J. William, 1941- (Princeton, New Jersey : Princeton University Press, 1999)
"One of the greatest mysteries in reconstructing the history of life on Earth has been the apparent absence of fossils dating back more than 550 million years. We have long known that fossils of sophisticated marine life-forms existed at the dawn of the Cambrian Period, but until recently scientists had found no traces of Precambrian fossils. The quest to find such traces began in earnest in the mid-1960s and culminated in one dramatic moment in 1993 when William Schopf identified fossilized microorganisms three and a half billion years old. This startling find opened up a vast period of time - some eighty-five percent of Earth's history - to new research and new ideas about life's beginnings. In this book, William Schopf, a pioneer of modern paleobiology, tells for the first time the exciting and fascinating story of the origins and earliest evolution of life and how that story has been unearthed."--Jacket
Darwin's dilemma -- Birth of a new field of science -- The oldest fossils and what they mean -- How did life begin? -- Metabolic memories of the earliest cells -- So far, so fast, so early? -- Stromatolites : earth's first high-rise condos -- Cyanobacteria : earth's oldest "living fossils" -- Cells like ours arise at last -- Solution to Darwin's dilemma -- Epilogue : Extraordinary claims! Extraordinary evidence? -- Fossils, foibles, and frauds -- The hunt for life on Mars
Includes bibliographical references and indexes.
Keywords: Life -- Origin; Evolutionary paleobiology; Paleontology -- Precambrian; Micropaleontology